Effectiveness of intermittent preventive treatment for malaria with sulfadoxine-pyrimethamine in women attending antenatal clinic at the University of Benin Teaching Hospital - Onuoha, Benice N.; Iweka, Reuben O.; Ande, Adedapo B.; Okonofua, Friday E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Intermittent preventive treatment for malaria using sulfadoxine-pyrimethamine (IPT-SP) is one of the methods proposed by the World Health Organization (WHO) to reduce the burden of malaria in pregnant women. This study evaluated the practice of IPT-SP in UBTH in terms of compliance with the WHO recommendations and maternal outcome; and to explore factors that may facilitate or hinder its implementation. Methods: This study was a mixed method, using the explanatory sequential design. The study population were 420 booked women at term selected randomly. A written informed consent was obtained. A semi-structured questionnaire was used to obtain data from personal identification card, case notes, and computerized system. Trained medical doctors collected information and peripheral blood samples for malaria parasite (MP) testing and packed cell volume (PCV) using rapid diagnostic test (RDT) kit and automated haemoglobinometer. The results were grouped into sub-optimal (IPT-SP <3) and optimal (IPT-SP ≥3). The qualitative study was an in-depth interview of stakeholders and focus group discussion with booked women not up to term receiving IPT-SP. Quantitative data were analysed using IBM SPSS with P <0.05; thematic analysis was used for qualitative data. Results: Of the 420 booked women, 60% (252) were given ≥3 doses while 40% (168) were given <3 doses. However, 17% (43) of those who collected ≥3 doses did not swallow up to 3 doses. Thus, 211 (50.2%) had suboptimal dosing while 209 (49.8%) had optimal dosing. A total of 45 (10.7%) were MP positive, of which 91.1% (41) had suboptimal dosing and 8.9% (4) had optimal dosing; (p<0.0001). A total of 30 (7.1%) had PCV<30%, out of which 83.3% (25) had suboptimal dosing (p<0.0001). Mean PCV in suboptimal group was 27.33±2.17 and 35.65±3.23 in optimal group; (p<0.001). Major factors were absence of directly observed therapy (DOT), ignorance and lack of proper knowledge among caregivers and recipients, while caregiver dedication was a positive factor. Conclusions: There is significant difference in maternal malaria parasitaemia and anemia between suboptimal and optimal IPT-SP dosing in UBTH. The impediments to IPT-SP distribution are comparatively easy to overcome.